Smart Home Energy Management Systems: A Literature survey - Gupta, A; Garg, T; Paygude, P (International Journal of Computer Sciences and Engineering, 2025)
India being a developing country produces a large amount of CO2, Major portion of which includes Electricity production. This paper aims to bring light to the technologies related to Smart Grid Systems and Smart homes which can be incorporated to reduce energy usage. Smart Grid is a technology to decentralize energy supply and communicate with users to dynamically set prices to reduce load on the power grid. Smart Home Technology automates and controls all electrical devices connected in the network. The combination of these two technologies can help reduce load on Power Grid and thus save energy consumption.